The organization of nuclear ribosomal DNA in gnetophytes – physically separate and physically linked arrangements of 35S and 5S genes. A commentary on: ‘Remarkable variation of ribosomal DNA organization and copy number in gnetophytes, a distinct lineage of gymnosperms’ - Renner, Susanne (Ann Bot, 2019)
This article comments on: Wencai Wang, Tao Wan, Hannes Becher, Alena Kuderova, Ilia J. Leitch, Sonia Garcia, Andrew R. Leitch and Aleš Kovařík. 2019. Remarkable variation of ribosomal DNA organization and copy number in gnetophytes, a distinct lineage of gymnosperms. Annals of Botany 123(5): 767–781.